The Impact of HLA Class I-Specific Killer Cell Immunoglobulin-Like Receptors on Antibody-Dependent Natural Killer Cell-Mediated Cytotoxicity and Organ Allograft Rejection - Rajalingam, Raja (Frontiers in Immunology, 2016)
Natural killer (NK) cells of the innate immune system are cytotoxic lymphocytes that play important roles following transplantation of solid organs and hematopoietic stem cells. Recognition of self HLA class I molecules by inhibitory killer cell immunoglobulin-like receptors (KIR) is involved in the calibration of NK cell effector capacities during a developmental stage, allowing the subsequent recognition and elimination of target cells with decreased expression of self HLA class I (due to virus infection or tumor transformation) or HLA class I disparities (in the setting of allogeneic transplantation). NK cells expressing an inhibitory KIR binding self HLA can be activated when confronted with allografts lacking a ligand for the inhibitory receptor. Following the response of the adaptive immune system, NK cells can further destroy allograft endothelium by antibody-dependent cell-mediated cytotoxicity (ADCC), triggered through cross-linking of the CD16 Fc receptor by donor-specific antibodies bound to allograft. Upon recognizing allogeneic target cells, NK cells also secrete cytokines and chemokines that drive maturation of dendritic cells to promote cellular and humoral adaptive immune responses against the allograft. The cumulative activating and inhibitory signals generated by ligation of the receptors regulates mature NK cell killing of target cells and their production of cytokines and chemokines. This review summarizes the role of NK cells in allograft rejection and proposes mechanistic concepts that indicate a prominent role for KIR-HLA interactions in facilitating NK cells for Fc receptor-mediated ADCC effector function involved in antibody-mediated rejection of solid organ transplants.